Statistical modeling of Ship's hydrodynamic performance indicator. (June 2021) - Gupta, Prateek; Taskar, Bhushan; Steen, Sverre; Rasheed, Adil
Abstract: The traditional method used to estimate the hydrodynamic performance of a ship uses either the model test results or one of the many empirical methods to estimate and observe the trend in fouling friction coefficient ( Δ C F ) over time. The biggest weakness of this method is that the model test results as well as the empirical methods used here is sometimes not well-fitted for the full-scale ship due to several reasons like scale effects and, therefore, this method may result in an inaccurate performance prediction. Moreover, in the case of a novel ship design, it would be nearly impossible to find a well-fitting empirical method. The current work establishes a new performance indicator, formulated in the form of generalized admiralty coefficient with displacement and speed exponents statistically estimated using the in-service data recorded onboard the ship itself. The current method completely removes the dependence on empirical methods or model test results for the performance prediction of ships. It is observed here that the performance predictions using the current method and the traditional method are based on the same underlying logic as well as the results obtained from both the methods are found to be in good agreement.